2007
DOI: 10.1074/jbc.m608045200
|View full text |Cite
|
Sign up to set email alerts
|

Src-dependent Phosphorylation of Membrane Type I Matrix Metalloproteinase on Cytoplasmic Tyrosine 573

Abstract: Membrane type 1 matrix metalloproteinase (MT1-MMP) is a transmembrane MMP that plays important roles in migratory processes underlying tumor invasion and angiogenesis. In addition to its matrix degrading activity, MT1-MMP also contains a short cytoplasmic domain whose involvement in cell locomotion seems important but remains poorly understood. In this study, we show that MT1-MMP is phosphorylated on the unique tyrosine residue located within this cytoplasmic sequence (Tyr The degradation of extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 47 publications
13
128
1
1
Order By: Relevance
“…Endothelial cells were treated with S1P, which is known to promote MT1-MMP translocation to the plasma membrane (Nyalendo et al, 2007). Western blot analyses confirmed Hic-5 silencing and enrichment of surface biotinylated molecules (determined using anti-PECAM1 antibodies), and no contamination from cytoplasmic proteins (by using GAPDH controls) (Fig.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Endothelial cells were treated with S1P, which is known to promote MT1-MMP translocation to the plasma membrane (Nyalendo et al, 2007). Western blot analyses confirmed Hic-5 silencing and enrichment of surface biotinylated molecules (determined using anti-PECAM1 antibodies), and no contamination from cytoplasmic proteins (by using GAPDH controls) (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Endothelial lumen formation is a crucial aspect of endothelial morphogenesis and tubulogenesis (Davis et al, 2011), and MT1-MMP is required for both successful lumen formation and endothelial cell sprouting into collagen matrices (Chun et al, 2004;Stratman et al, 2009;Sacharidou et al, 2010). S1P has been shown to stimulate phosphorylation of MT1-MMP at Y573 (Nyalendo et al, 2007). Because a link between MT1-MMP and Hic-5 has not been established, we first investigated whether Hic-5 colocalized with phosphorylated MT1-MMP ( pMT1-MMP Y573) in endothelial cells in response to activating stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MT1-MMP ICD further undergoes palmitoyla-tion at Cys 574 , a lipid post-translational modification that was shown to modulate cell migration and clathrin-mediated internalization (34). Recently, it has been reported that MT1-MMP is phosphorylated within its ICD at Tyr 573 in an Src-dependent mechanism (35). Expression of a non-phosphorylable MT1-MMP Tyr 573 mutant in fibrosarcoma cells resulted in impaired levels of proliferation within three-dimensional type-I collagen gels (36).…”
Section: Membrane Type 1 Matrix Metalloproteinase (Mt1-mmp/ Mmp14mentioning
confidence: 99%
“…Remaining co-localization was still detected, indicating an overlap in the localization of both proteins although without direct interaction. in a Src-or PKC-dependent manner (35,37), which may be a prerequisite for protein ubiquitination (47). To test whether MT1-MMP phosphorylation affects its ubiquitination, MT1-MYC-Y573A and MT1-MYC-T567A mutants were used.…”
Section: Mt1-mmp Is Monoubiquitinated At Itsmentioning
confidence: 99%